2008
DOI: 10.1016/j.jhep.2007.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Small proline-rich proteins (SPRR) function as SH3 domain ligands, increase resistance to injury and are associated with epithelial–mesenchymal transition (EMT) in cholangiocytes

Abstract: Background/Aims-Deficient biliary epithelial cell (BEC) expression of small proline rich protein (SPRR) 2A in IL-6-/-mice is associated with defective biliary barrier function after bile duct ligation. And numerous gene array expression studies show SPRR2A to commonly be among the most highly upregulated genes in many non-squamous, stressed and remodeling barrier epithelia. Since the function of SPRR in these circumstances is unknown, we tested the exploratory hypothesis that BEC SPRR2A expression contributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 60 publications
4
55
0
1
Order By: Relevance
“…Small proline rich protein 2a (SPRR2a) overexpression in CCA cells induced EMT, which in turn promotes invasiveness [59,120]. Further experiments showed that SPRR2A acts as a transcriptional corepressor with ZEB1 to repress miR-200c/141 transcription in CCA cells in order to maintain a mesenchymal phenotype [59].…”
Section: Additional Regulatory Factorsmentioning
confidence: 99%
“…Small proline rich protein 2a (SPRR2a) overexpression in CCA cells induced EMT, which in turn promotes invasiveness [59,120]. Further experiments showed that SPRR2A acts as a transcriptional corepressor with ZEB1 to repress miR-200c/141 transcription in CCA cells in order to maintain a mesenchymal phenotype [59].…”
Section: Additional Regulatory Factorsmentioning
confidence: 99%
“…EMT is a complex process that involves cross talk among several signaling pathways that collaborate to affect global, but gradual, changes in cell structure and function [56] . In this dynamic process cells eventually lose their typical epithelial characteristics (proteins that mediate cell-cell, cell-matrix contacts and cytoskeletal organization) [57,58] . These changes cause epithelial cells to disassociate from their neighbors, gradually acquire a motile phenotype, and eventually migrate out of epithelial sheets and into adjacent mesenchyme [21,56] .…”
Section: Epithelial-to-mesenchymal Transition (Emt)mentioning
confidence: 99%
“…The process of EMT has received great attention and its role in kidney fibrosis has been studied extensively in recent years 13,14 . Moreover, the EMT concept has been successfully translated to liver fibrogenesis 1521 . Especially in cholestatic liver diseases and their corresponding animal models EMT, namely from bile duct epithelial cells into myofibroblasts, is supposed to play a pivotal role in the initiation and perpetuation of liver fibrosis 15,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the EMT concept has been successfully translated to liver fibrogenesis 1521 . Especially in cholestatic liver diseases and their corresponding animal models EMT, namely from bile duct epithelial cells into myofibroblasts, is supposed to play a pivotal role in the initiation and perpetuation of liver fibrosis 15,17 . As such, previous studies in the DDC-fed mouse model showed pronounced induction of hepatic OPN in BECs (including BECs in reactive ductules) and hepatocytes in acinar zone 1 according to those lobular regions where adjacent porto-portal septa develop in later in the disease course 6 .…”
Section: Introductionmentioning
confidence: 99%